The origin of tetraradial symmetry in cnidarians. (25th January 2017) - Dzik, Jerzy; Baliński, Andrzej; Sun, Yuanlin
Abstract : Serially arranged sets of eight septa‐like structures occur in the basal part of phosphatic tubes of Sphenothallus from the early Ordovician (early Floian) Fenxiang Formation in Hubei Province of China. They are similar in shape, location and number, to cusps in chitinous tubes of extant coronate scyphozoan polyps, which supports the widely accepted cnidarian affinity of this problematic fossil. However, unlike the recent Medusozoa, the tubes of Sphenothallus are flattened at later stages of development, showing biradial symmetry. Moreover, the septa (cusps) in Sphenothallus are obliquely arranged, which introduces a bilateral component to the tube symmetry. This makes Sphenothallus similar to the Early Cambrian Paiutitubulites, having similar septa but with even more apparent bilateral disposition. Biradial symmetry also characterizes the Early Cambrian tubular fossil Hexaconularia, showing a similarity to the conulariids. However, instead of being strictly tetraradial like conulariids, Hexaconularia shows hexaradial symmetry superimposed on the biradial one. A conulariid with a smooth test showing signs of the 'origami' plicated closure of the aperture found in the Fenxiang Formation supports the idea that tetraradial symmetry of conulariids resulted from geometrical constrains connected with this kind of closure. Its minute basal attachment surface makes it likely that the holdfasts characterizing Sphenothallus and advanced conulariids are secondary features. This concurs with the lack of any such holdfast in the earliest Cambrian Torellella, as well as in the possibly related Olivooides and Quadrapyrgites . Bilaterally arranged internal structures in polyps representing probably the oldest medusozoans support the suggestions based on developmental evidence that the ancestor of cnidarians also was a bilaterally symmetrical animal. This is one more example of fossil data that strictly fit the molecular phylogenetic evidence but not necessarily morphology‐based zoological interpretations.